2021
DOI: 10.14814/phy2.14839
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxia causes senescence and increases glycolysis in cultured lung epithelial cells

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…The phosphorylation event of p53 at S15 in humans and S18 in mice is able to increase its recruitment on the p21 promoter, thereby augmenting p21 gene expression 41 , 42 . Our recent report showed that p53 deletion inhibits hyperoxia-induced senescence in cultured lung epithelial cells 15 . Thus, an activated phosphorylated p53/p21 pathway contributes to developmental and hyperoxia-induced lung senescence.…”
Section: Discussionmentioning
confidence: 97%
“…The phosphorylation event of p53 at S15 in humans and S18 in mice is able to increase its recruitment on the p21 promoter, thereby augmenting p21 gene expression 41 , 42 . Our recent report showed that p53 deletion inhibits hyperoxia-induced senescence in cultured lung epithelial cells 15 . Thus, an activated phosphorylated p53/p21 pathway contributes to developmental and hyperoxia-induced lung senescence.…”
Section: Discussionmentioning
confidence: 97%
“…Senescent cells are generally identified by a combination of indicators including an absence of proliferation markers, loss of the nuclear lamina protein lamin B1, increased senescence-associated β galactosidase, increased expression of cell-cycle inhibitors, such as the cyclin-dependent kinase inhibitors p21 and p16, as well as evidence of DNA damage [ 37 ]. We previously reported that hyperoxia causes senescence in MLE-12 cells [ 28 ]. This is associated with increased double-stranded DNA damage, p53 phosphorylation and nuclear localization.…”
Section: Discussionmentioning
confidence: 99%
“…This is associated with increased double-stranded DNA damage, p53 phosphorylation and nuclear localization. Furthermore, hyperoxia-induced senescence was p53-dependent, but not pRB-dependent, in these cells [ 28 ]. Nuclear lamin B1 exclusion is a robust hallmark of senescence in culture and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that cellular senescence in the alveolar epithelium contributes to the pathogenesis and progression of BPD [ 36 , 37 ]. This study identified a significant upregulation of Serpine1 in the lung tissue of neonatal mice with IUI.…”
Section: Discussionmentioning
confidence: 99%